2018
DOI: 10.14196/mjiri.32.21
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of Phenylalanine hydroxylase gene in Iranian patients with Phenylketonuria

Abstract: Background: Phenylketonuria as the most common genetic metabolic disorder is the result of disruption of the phenylalanine hydroxylase gene. This study was carried out to explore the phenylalanine hydroxylase gene mutation status of Iranian phenylketonuria patients. Methods: Blood samples were collected from 30 patients, and hot spot areas of the phenylalanine hydroxylase gene, including exons 6, 7, 8, 11, and 12 were studied through polymerase chain reaction and sequencing techniques. Results: Eight differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The symbol "#" in superscript represents unreported, and "-" represents no mutation or not checked out. Zhang et al, 2018), the c.1222C > T mutation is the most common in the United States (Kaul et al, 1994), c.1238G > C is common in Japan (Okano et al, 2011), and IVS10-11G > A is the most common in Iran and Spain (Bueno et al, 2013;Rastegar Moghadam et al, 2018). In the present study, eight kinds of 12 mutation sites were found in the PHA gene: c.1174T > A, c.1223G > A, c.208_210del, c.611A > G, c.331C > T, c.728G > A, c.320A > G, and c.721C > T. Further, c.1223G > A was the most common PAH mutation site, accounting for 25% of all mutation types, potentially representing a hot spot mutation in this region.…”
Section: Discussionmentioning
confidence: 99%
“…The symbol "#" in superscript represents unreported, and "-" represents no mutation or not checked out. Zhang et al, 2018), the c.1222C > T mutation is the most common in the United States (Kaul et al, 1994), c.1238G > C is common in Japan (Okano et al, 2011), and IVS10-11G > A is the most common in Iran and Spain (Bueno et al, 2013;Rastegar Moghadam et al, 2018). In the present study, eight kinds of 12 mutation sites were found in the PHA gene: c.1174T > A, c.1223G > A, c.208_210del, c.611A > G, c.331C > T, c.728G > A, c.320A > G, and c.721C > T. Further, c.1223G > A was the most common PAH mutation site, accounting for 25% of all mutation types, potentially representing a hot spot mutation in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Some hotspot mutations exist in PAH gene and vary in different populations. For example, the most common PAH mutation is c.1222C > T in American (Kaul et al, 1994), IVS10-11G > A in Iranian (Zamanfar et al, 2017; Esfahani and Vallian, 2018; Rastegar Moghadam et al, 2018) and Spanish (Bueno et al, 2013; Aldámiz-Echevarría et al, 2016), c.168+5G > C in western Iranian (Alibakhshi et al, 2014), c.1238G > C in Japanese (Okano et al, 2011; Dateki et al, 2016), c.728G > A in Chinese (Zhou et al, 2012; Li et al, 2015; Zhang et al, 2018), c.781C > T in Karachays (Gundorova et al, 2018), c.1068C > A and c.728G > A in south Korean (Lee et al, 2008), c.1162G > A in Brazilian (Vieira Neto et al, 2018), c.782G > A in Syrian (Murad et al, 2013), and c.1222C > T in Australian (Ho et al, 2014). These different hotspot mutations suggested different origins.…”
Section: Discussionmentioning
confidence: 99%
“…This variant consists of an alteration in a conserved nucleotide at position 261, where the aromatic amino acid hydroxylase is located, in the C-terminal of the phenylalanine-4-hydroxylase protein. This variant has been associated with benign hyperphenylalaninemia and classic phenylketonuria requiring dietary treatment [51,52], and has an allelic frequency of 5.3-5.5% [53,54]. In vitro studies have shown that the c.782G > A variant alters the function of the protein and that the resulting enzyme retains a residual level of activity (6.3-11%), which may explain the moderate phenotype associated with the variant [55].…”
Section: Discussionmentioning
confidence: 99%